EDEMATOUS PAPULES. INFANTILE URTICARIA. - Garofalo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Urticaria is one of the most frequent reactions of the skin to various stimuli. From a pathological point of view, it is characterized by a transitory vasodilatation leading to plasma leaking from the dermal and subcutaneous vessels. The clinical consequence of these events is the weal, namely a pathognomonic lesion which can be detected only in urticaria. The edema is more marked when urticaria affects the eyelids, lip and prepuce, justifying the term of angioedema.